Searching Inorganic Substances in SciFinder. - A. Ben Wagner (Issues in Science and Technology Librarianship)
The primary goal of this article is to assist researchers and librarians to accurately and completely search Chemical Abstracts Service's (CAS) SciFinder web-based system for inorganic substances, excepting coordination compounds. CAS indexing policies and conventions in handling the wide variety of inorganic materials are described in detail. Detailed search strategies for retrieving salts, oxides, sulfides, minerals, alloys, metal clusters, tabular inorganics, indeterminate derivatives, and unknown/variable compositions are reviewed. Although this article is of primary value for SciFinder researchers, the analysis of how CAS handles inorganics will be of use to searchers regardless of the platform used to access Chemical Abstracts information. [ABSTRACT FROM AUTHOR]